Psychological intervention change measurement in Latin America: Where from? Where to?. (2nd January 2021) - Paz, Clara; Mascialino, Guido; Proaño, Karen; Evans, Chris
ABSTRACT: Objective: To conduct a scoping review of measure utilization in Latin America. We relate the findings to the needs of the region and give recommendations for measure usage in LA. Methods: Six electronic databases (PubMed, Web of Science, CINAHL, PsychInfo, SCOPUS, and SCIELO) were searched to identify peer-reviewed literature. In total, 207 studies using change and/or outcome measures were identified based on a priori inclusion criteria. Results: Production by country varied markedly; more than three quarters of the studies took place in just three of the 20 Latin American countries: Brazil, Chile, and Mexico. The most frequently used measures were the Outcome Questionnaire, Beck Depression Inventory-II, Hamilton Rating Scale, and Yale-Brown Obsessive-Compulsive Scale. The most common diagnosis was depression ( n = 54). Conclusions: Outcome and change research in Latin America is growing rapidly but future efforts should focus more tightly on the needs of the region, as well as on forging collaborations with researchers from other regions. The use of change measures for serial assessment throughout interventions is recommended in view of its adaptability to highly diverse Latin American social realities. Dissemination of research findings and promotion of outcome and change measure use through implementation of public policy is recommended.